The Implementation Of One Stop Integrated Services (LTSA) At The Manpower Office Of Gianyar Regency - Jayadi Putra, I Made Ngurah Bangun; Darma, Gede Sri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Local government, through the Manpower Office, has implemented LTSA to enhance service efficiency for Indonesian Migrant Workers (PMI). However, the implementation still faces challenges such as procedures that are not well-integrated between agencies, limited human resources, and technical issues in the SISNAKER service system. Furthermore, the prevalence of illegal departures of PMI underscores the need for public education on correct procedures and available protections. This research aims to provide an overview of the On The Spot One Get Service (LTSA) implementation at the Gianyar District Manpower Office. This study uses a descriptive qualitative research method with an inductive approach. The sample selection technique employs purposive sampling. Informants include the Head of the Gianyar District Manpower Office, the Secretary, the Head of the Manpower Placement and Job Opportunity Expansion Division, and the community. The results indicate that LTSA is currently limited to labor services and has not been integrated with other services such as population services, police services, immigration services, and health services. Budget constraints and infrastructure conditions are contributing factors. The Head of the Gianyar District Manpower Office plays a strategic role in LTSA implementation, overseeing service procedures aligned with the office's vision, mission, and goals. The office is focused on enhancing internal capacity through improving staff competencies and proposing budgets for integrating LTSA services and upgrading technical infrastructure.